Study of optimisation strategies for aircraft structural design - Huang, Feng (Cranfield University, 2012)
Optimisation plays an important role in structural design. Structural design optimisation is not only a matter of weight reduction of the structure; it can be used to optimise any type of objectives. In engineering practise, it is also common to maximise performance parameters such as the maximum load capacity and the fatigue life of a structure. Besides, the structural design in modern commercial aircrafts inevitably involves considerations such as aerodynamic performance and system requirements. Therefore the optimisation of structural design usually has various disciplines to be taken account of. Hence, the single objective, multi-objective and multi-disciplinary optimisation problems are very important in engineering practise. The aims of this research project are to classify and summarise typical optimisation applications and their objectives and constraints in aircraft structural design to help engineers to solve their optimisation problems. In addition, this study aims to develop a systematic framework and recommendations for approaches to various problems in this domain to inspire engineers to solve their optimisation problems. To achieve this objective, a literature review is carried out, focussing on four aspects: Modelling of CAD structures, Finite element analysis of structures, Structural Optimisation and Mathematical Optimisation. In addition, a survey was undertaken with 15 experts with different backgrounds from Europe and other countries. Meanwhile, three experts in aerospace industry are called for an interview. This thesis also presents the engineering applications in various aircraft components. The fuselage component multi-disciplinary (structural, acoustics and thermal) optimisation is discussed. In terms of the wing component, the space unit of the wing box is defined for optimisation, and different constraints for different parts are summarised. In addition, brief introduction of other component optimisations are introduced. This thesis also presents the development of a systematic framework for the aircraft structural optimisation approaches. The general approach, and the DOE & Algorithmic approach are defined and adopted in the framework. A framework chart is illustrated to help engineers to initialise their problems in the initial phase and cope with them following the workflow of the framework chart. In order to highlight useful and practical suggestions for the engineers and designers, recommendations are presented in this thesis. Case studies are carried out to demonstrate and validate the function of the framework. There are three case studies in this thesis, and all of them are from industries. The first one is a door hinge with single-objective topology optimisation problem. The second one is a crank with multi-objective shape optimisation problem. And the third one is a landing gear torsion link with a combined (topology, shape and sizing) optimisation problem. HYPERWORKS is adopted to conduct the optimisation, which includes built-in parameterised tools to generate the mesh solver, carry out the finite element analysis, and optimise the design with various algorithms. This study indicates that the optimisation is not always applicable in every phase of the design. The preliminary phase is crucial for the entire optimisation. The optimisation framework developed in this study can be systematically applied in aircraft structural design. Engineers should learn about the DOE and algorithmic approach in order to solve the multi-objective or multi-disciplinary problem, and the approach framework developed in this study could provide a good guideline.
Keywords: Aircraft; Structural; Design; Optimisation; Strategies; Single objective; Mono-objective; Multi-objective; Multi-disciplinary; constraint; workflow